Transferability of principles of evidence based medicine to improve educational quality: systematic review and case study of an online course in primary health care. - Greenhalgh, T; Toon, P; Russell, J; Wong, G; Plumb, L; Macfarlane, F (2003)
The success of evidence based medicine has led to pressure to make medical education more evidence based. Greenhalgh and colleagues tested the transferability, of these principles when developing a postgraduate course.